2011
DOI: 10.5194/angeo-29-1-2011
|View full text |Cite
|
Sign up to set email alerts
|

Sq field characteristics at Phu Thuy, Vietnam, during solar cycle 23: comparisons with Sq field in other longitude sectors

Abstract: Abstract. Quiet days variations in the Earth's magnetic field (the Sq current system) are compared and contrasted for the Asian, African and American sectors using a new dataset from Vietnam. This is the first presentation of the variation of the Earth's magnetic field (Sq), during the solar cycle 23, at Phu Thuy, Vietnam (geographic latitudes 21.03 • N and longitude: 105.95 • E). Phu Thuy observatory is located below the crest of the equatorial fountain in the Asian longitude sector of the Northern Hemisphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…The equinoctial asymmetry in the EEJ strengths during the two equinoxes (i.e., spring and autumn) is also evident in Figures 2c and 2d. This could be attributed to the changes in relative strength of northern and southern Sq current cells, which contribute to the equatorial electrojet in the Asian/Indian sector [Pham Thi Thu et al, 2011]. The averaged EEJ strength is similar for both IQD and IDD (Figure 3).…”
Section: Discussionmentioning
confidence: 91%
“…The equinoctial asymmetry in the EEJ strengths during the two equinoxes (i.e., spring and autumn) is also evident in Figures 2c and 2d. This could be attributed to the changes in relative strength of northern and southern Sq current cells, which contribute to the equatorial electrojet in the Asian/Indian sector [Pham Thi Thu et al, 2011]. The averaged EEJ strength is similar for both IQD and IDD (Figure 3).…”
Section: Discussionmentioning
confidence: 91%
“…Lanchester et al [2009] demonstrated the strength of the method by determining the peak energy and flux of the precipitation forming a number of dynamic auroral events with widths of the order of 100 m perpendicular to the geomagnetic field. Dahlgren et al [2011] used the technique in an investigation of the role of sheared aurora at boundary regions. In the study, it was found that a thin, sheared auroral arc appeared on the boundary between two different precipitating electron populations of different energies, where an energy gradient and increased number flux were present.…”
Section: Energy and Energy Flux Of Dynamic Auroramentioning
confidence: 99%
“…References [26] [27] [28] show that enhanced cowling conductivity along the magnetic equator is a major cause of EEJ. Figure 4 shows the that could exist between the Sq amplitude and the solar cycle variation as [9] had demonstrated in his works. observed at the Yaoundé station shows a unique variation pattern for the different months and seasons (see Figure 3 and Figure 6).…”
Section: E Honoré Et Almentioning
confidence: 80%
“…The diurnal and seasonal variations of the solar quiet (Sq) variations had been analyzed recently by several researchers [9] [10]. In this paper, we continue this analysis using the data provided by the Yaoundé station during quiet magnetic days from 2011 to 2014 in order to characterize it.…”
Section: Introductionmentioning
confidence: 94%